Assessing the Prevalence of Risk Factors for Neglected Tropical Diseases in Brazos County, Texas - Horney, Jennifer (PLoS Curr, 2017)
INTRODUCTION: Although more than one billion people live at risk of neglected tropical diseases (NTDs) in areas of Asia, sub-Saharan Africa, and Latin America, the degree to which they burden countries like the U.S. is unclear. Even though many NTDs such as dengue, leishmaniasis, and Chagas disease are typically not endemic to the U.S., the possibility of their emergence is noteworthy, especially in states like Texas with high levels of poverty, large immigrant populations, geographic proximity to endemic areas, and a climate amenable to the vectors for these diseases. Despite the health threat that emerging NTDs may pose, little is known about the prevalence of risk factors for NTDs in the U.S. METHODS: We tested the Community Assessment for Public Health Emergency Response (CASPER) method to assess the prevalence of risk factors for NTDs in Brazos County, Texas. Results: We found relatively low prevalence of risk factors related to travel (5.2% of respondents visited an endemic area in the previous 3 months); however, few respondents reported adherence to mosquito prevention, such as wearing long sleeves and long pants (14.1%, 95% CI: 13.9,14.4) and repellant containing DEET (13.5%, 95% CI: 13.2,13.7). Between 5.4% and 35.8% of respondents had a visible container (e.g., pet water dishes, flower pots, bird baths) that could support mosquito breeding. DISCUSSION: CASPER findings present public health authorities with potential avenues for implementing health education and other interventions aimed at reducing exposure to risk factors for NTDs among Texas residents.